The Influence of Content and System Quality, Sales Promotion and Convenience Towards Freemium Platform Satisfaction - Faranita Mustikasari; Bima Maryanto Putra; Levina Chrisa Anjani Setiawan; Rasyidah Ardelia Yuliani (DINASTI RESEARCH, 2026)
This study examines how content quality, system quality, sales promotion, and convenience can affect resubscription intention of the Freemium Over the Top platform. Users of this platform has free but limited access or paid with premium features and can subscribe to more than one platform. Hence, user loyalty is reflected as resubscription. The churn rate on Freemium is higher than the subscription Video on Demand platform, because customers can return to the free service at any time. It becomes challenge for the Freemium Over the Top to maintain its customer base, especially their subscriber. This study uses a quantitative method with 300 nonprobability - convenience sampling respondents, who have subscribed to Over the Top for at least 1 month. Data analysis using Partial Least Square with the results that content quality, system quality, sales promotion, convenience can affect customer satisfaction levels and resubscription intentions. This study also found that users have different preferences, and understanding these preferences can increase user conversion from free to paid. The results of this study can help business actors in the Freemium Over the Top to increase users’ satisfaction and desire to resubscribe.